Osteological description of Pseudopaludicola canga with implications for the taxonomic position of this taxon - Cardozo, Dario Elbio (2012)
Pseudopaludicola canga was described by Giaretta & Kokubum (2003) based on 74 individuals previously assigned to P. mystacalis by Lobo (1995). In the diagnosis of P.  canga, the original authors assigned the presence of terminal T-shaped phalanges as a character state for this taxon. However, the osteology of P. canga is not described and the presence of toe tips not expanded laterally is a characteristic share with all members of Pseudopaludicola unassigned to any group. In this work is describe for first time the osteology of P. canga, re-examining the external morphology providing a new diagnosisand establishing the taxonomic position of P. canga in the framework of phylogenetic hypothesis proposed by Lobo (1995). Additionally, is compared the toe tip digit IV, between P. falcipes and all the species included in the P. pusilla group and updated the type locality of P. canga. The osteology reveals that P. canga has the toe tips not T-shaped as mentionedby the original authors and this characteristic has important consequences for the diagnosis of the species. Additionally, the erroneous inclusion of P. canga in the P. pusilla group is confirmed by the phylogenetic analysis.